2020
DOI: 10.1002/jimd.12248
|View full text |Cite
|
Sign up to set email alerts
|

A biallelic pathogenic variant in the OGDH gene results in a neurological disorder with features of a mitochondrial disease

Abstract: 2‐Oxoglutarate dehydrogenase (OGDH) is a rate‐limiting enzyme in the mitochondrial TCA cycle, encoded by the OGDH gene. α‐Ketoglutarate dehydrogenase (OGDH) deficiency was previously reported in association with developmental delay, hypotonia, and movement disorders and metabolic decompensation, with no genetic data provided. Using whole exome sequencing, we identified two individuals carrying a homozygous missense variant c.959A>G (p.N320S) in the OGDH gene. These individuals presented with global development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Diminished OGDHc activity and mitochondrial abnormalities have been correlated with numerous neurodegenerative disorders, including Alzheimer’s disease, however, a link between reductions in the mitochondrial TCA cycle enzymes and (neuro) degeneration has not been established so far [ 1 , 2 , 3 , 4 ]. Recently, a biallelic pathogenic variant in OGDH gene leading to deficient 2-oxoglutarate dehydrogenase (E1o, the first component of the OGDHc, also known as OGDH) was reported in individuals with a neurological disorder resembling mitochondrial disease [ 5 ]. While rare in OGDH , whole-exome sequencing and rare variant burden analysis determined an overabundance of putative, potentially damaging mutations in the OGDHL (OGDH-like) and DHTKD1 genes across multiple patients with eosinophilic esophagitis (EoE), a chronic allergic disorder that presents in infancy and in adulthood [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diminished OGDHc activity and mitochondrial abnormalities have been correlated with numerous neurodegenerative disorders, including Alzheimer’s disease, however, a link between reductions in the mitochondrial TCA cycle enzymes and (neuro) degeneration has not been established so far [ 1 , 2 , 3 , 4 ]. Recently, a biallelic pathogenic variant in OGDH gene leading to deficient 2-oxoglutarate dehydrogenase (E1o, the first component of the OGDHc, also known as OGDH) was reported in individuals with a neurological disorder resembling mitochondrial disease [ 5 ]. While rare in OGDH , whole-exome sequencing and rare variant burden analysis determined an overabundance of putative, potentially damaging mutations in the OGDHL (OGDH-like) and DHTKD1 genes across multiple patients with eosinophilic esophagitis (EoE), a chronic allergic disorder that presents in infancy and in adulthood [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate synthase [ 12 ] and oxoglutarate dehydrogenase (OGDH) [ 13 ] catalyze the condensation of acetyl-CoA from glycolysis or other dissimilatory reactions with oxaloacetate to synthesize citric acid. They are the rate-limiting enzymes in the mitochondrial tricarboxylic acid (TCA) cycle and participate in many important biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that OGDH is associated with cell damage after cardiac ischemia perfusion (10), and has previously been reported to be associated with developmental delay, hypotonia, dyspraxia, and metabolic decompensation (11)(12)(13)(14). Recently, mutations in OGDH have been reported to cause global growth retardation, lactic acid elevation, ataxia, and seizures (15). However, there is no clear evidence that changes in OGDH expression are associated with various types of inflammation.…”
Section: Introductionmentioning
confidence: 99%